Sustaining the Financial Value of Global CSR: Reconciling Corporate and Stakeholder Interests in a Less Regulated Environment. (March 2014) - Blodgett, Mark S.; Hoitash, Rani; Markelevich, Ariel
Abstract In this article we examine the association between corporate social responsibility (CSR) and firm value. This line of research is important since firms continue to invest in CSR even though past studies reveal a limited linkage between financial value and CSR. However, the business case for CSR or "doing good while making a profit, " appears to be advancing within the business ethics literature as a preferred conception of CSR. We conjecture that the greater unification and refinement of both profit maximization and stakeholder interests through corporate acts, not statements alone, will sustain the financial value of CSR in a less regulated global business environment. We study the triangle of what companies say, what companies do, and firm financial performance. We analyze Fortune 250 firms and find a positive association between what companies do based on KLD Research and Analytics, Inc. (KLD) ratings, and what companies state about ethics in their CSR statements. We then employ regression analysis and find that companies' socially responsible acts are positively associated with overall firm value and financial performance. Yet we do not find a statistically significant association between what companies say regarding ethics in their CSR statements and their financial outcomes. These results suggest that firm value and financial performance is associated with what companies do and not what they say. Our results seem to be driven by multinational corporations (MNCs) and not by non‐MNCs. This is possibly because MNCs generally operate in a less regulated global business environment that often necessitates strong ethical corporate leadership to further stakeholder interests. Overall, these results help reconcile corporate and stakeholder objectives since evidence of a link between financial performance and doing good sustains global CSR.